Stochastic Volatility and Pricing Bias in the Swedish OMX-Index Call Option Market - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2000)
This paper investigates the pricing bias in the Swedish OMX-Index Option market and how a stochastic volatility affects European call option prices. The market is purely European and without dividends for the period studied. A CIR square-root process for the volatility is estimated with non-linear least square minimization, and stochastic volatility option prices are calculated through Fourier-Inversion. These call option prices are compared to Black-Scholes prices as well as observed market prices, and a well-defined bias structure between Stochastic Volatility prices and Black-Scholes prices is observed. With a dynamic hedging scheme, I demonstrate larger (ex ante) profits, excluding transaction costs, for traders using the stochastic volatility model rather than the Black-Scholes model
Keywords: C52; G13; 330; derivatives pricing; stochastic volatility; Fourier inversion